2018
DOI: 10.32598/jpcp.6.4.231
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Cognitive Group Therapy on Self-efficacy and Depression Among Divorced Women

Abstract: This research aimed to determine the effectiveness of cognitive group therapy on self-efficacy and depression among divorced women. Methods: This was a quasi-experimental study with pretest-posttest design with control group. In this study, all divorced women referring to Hazrate Zeinab Charity Institution in Varamin City, Iran were considered as the statistical population with a sample size of 30 subjects who were selected via purposive sampling and randomly assigned to the experimental (n=15) and control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Also, in the research by Najafi and Fouladchang, its reliability was reported as .80. In Iran, the validity and reliability of the questionnaire were confirmed by Barati Bakhtiari at 79% and also in the research by Malek Shahi and colleagues at 73% (Asadpour & Sadat Hosseini, 2018;Azimi, 2012).…”
Section: Self-efficacymentioning
confidence: 72%
See 1 more Smart Citation
“…Also, in the research by Najafi and Fouladchang, its reliability was reported as .80. In Iran, the validity and reliability of the questionnaire were confirmed by Barati Bakhtiari at 79% and also in the research by Malek Shahi and colleagues at 73% (Asadpour & Sadat Hosseini, 2018;Azimi, 2012).…”
Section: Self-efficacymentioning
confidence: 72%
“…Selfefficacy is an individual's cognitive state regarding whether they can perform the necessary behaviors to achieve a desired outcome (Bandura, 1977(Bandura, , 1982. Self-efficacy can also be considered as an individual's confidence in their capability within a specific domain (Asadpour & Sadat Hosseini, 2018;Parsakia et al, 2023). Self-efficacy applied to marital relationships is a way to conceptualize an individual's confidence in their ability to perform relationship-affirming behaviors such as open communication with a spouse, providing support and care, and/or controlling emotions and anger (Mashal pour fard et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Before the intervention, the members of the experimental and control groups answered the Luthans psychological capital questionnaire in the form of a pre-test. After the necessary coordination, narrative therapy training sessions based on Lopez et al's treatment protocol [24] were held in 8 sessions of 50 minutes, twice a week, in groups, observing health protocols and maintaining social distancing to prevent the spread of the coronavirus.…”
Section: Methodsmentioning
confidence: 99%
“…This protocol is based on Lopez et al, studies of 2014, which was used by Jafari et al [24] (Table 1). Data were collected using the Luthans psychological capital questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Still, studies have shown that women with stress experience more negative emotions than men, and the prevalence of depression is higher in women than men [ 16 ]. Asadpour and Hosseini [ 17 ] also illustrated that divorced women often suffer from negative feelings such as guilt, depression, and distress; according to Chen et al [ 18 ], those who lose their intimate relationships, in addition to experiencing depression, would face more severe problems such as drug and alcohol abuse and suicidal thoughts.…”
Section: Introductionmentioning
confidence: 99%